2016
DOI: 10.1007/s12519-016-0013-2
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics prophylaxis in pyelonephritis infants with normal urinary tracts

Abstract: Probiotic prophylaxis was more effective in infants with pyelonephritis and normal urinary tract than in those with no-prophylaxis. It could be used as a natural alternative to antibiotic prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 39 publications
1
7
0
1
Order By: Relevance
“…23 Probiotic prophylaxis of Lactobacillus species was as effective in infants with pyelonephritis and normal urinary tract as antibiotic prophylaxis with trimethoprim/sulfamethoxazole. 24 Lee and Lee also obtained the same results in infants with primary VUR and recurrent UTI. 25 With regards to the limitations of the study, only children admitted to the present hospital due to UTI were enrolled, hence there was a selection bias.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…23 Probiotic prophylaxis of Lactobacillus species was as effective in infants with pyelonephritis and normal urinary tract as antibiotic prophylaxis with trimethoprim/sulfamethoxazole. 24 Lee and Lee also obtained the same results in infants with primary VUR and recurrent UTI. 25 With regards to the limitations of the study, only children admitted to the present hospital due to UTI were enrolled, hence there was a selection bias.…”
Section: Discussionsupporting
confidence: 54%
“…Apart from antibiotic treatment, vitamin A supplementation was proven to be efficient in decreasing renal scarring secondary to acute pyelonephritis and in relieving symptoms such as fever, urinary frequency and poor feeding duration in girls with acute pyelonephritis . Probiotic prophylaxis of Lactobacillus species was as effective in infants with pyelonephritis and normal urinary tract as antibiotic prophylaxis with trimethoprim/sulfamethoxazole . Lee and Lee also obtained the same results in infants with primary VUR and recurrent UTI …”
Section: Discussionmentioning
confidence: 80%
“…Probiotics have been used for the prevention of UTI in children and adults [52, 142, 143]. A 2017 Cochrane meta-analysis of 6 randomized and quasi-randomized controlled studies involving 352 children and adults with UTI found no significant reduction in the risk of recurrent UTI between patients treated with probiotics and placebo (risk ratio: 0.82; 95% confidence interval: 0.60 to 1.12) with wide confidence intervals [143].…”
Section: Prophylaxismentioning
confidence: 99%
“…Although not statistically significant, probiotics also resulted in lower UTI rates than the antibiotic group. The resistance rates of E. coli were much lower in the probiotic group than in the other two groups (23). However, there are some rare reports that probiotics may lead to serious infections both in immunocompetent and immunocompromised patients and the detection of causative agent is difficult as they are usually regarded as contaminants.…”
Section: Trials On the Current Conceptmentioning
confidence: 87%